Systemic and cerebrospinal fluid immune and complement activation in Ugandan children and adolescents with long-standing nodding syndrome: A case-control study - Ogwang, Rodney; Muhanguzi, Dennis; Mwikali, Kioko; Anguzu, Ronald; Nutman, Thomas B.; Newton, Charles R.; Idro, Richard (Epilepsia Open, 2021)
Nodding syndrome is a poorly understood epileptic encephalopathy characterized by a unique seizure type—head nodding—and associated with Onchocerca volvulus infection. We hypothesized that altered immune activation in the cerebrospinal fluid (CSF) and plasma of children with nodding syndrome may yield insights into the pathophysiology and progression of this seizure disorder. We conducted a case-control study of 154 children (8 years or older) with long-standing nodding syndrome and 154 healthy age-matched community controls in 3 districts of northern Uganda affected by nodding syndrome. Control CSF samples were obtained from Ugandan children in remission from hematological malignancy during routine follow-up. Markers of immune activation and inflammation (cytokines and chemokines) and complement activation (C5a) were measured in plasma and CSF using ELISA or Multiplex Luminex assays. O volvulus infection was assessed by serology for anti–OV-16 IgG levels. The mean (SD) age of the population was 15.1 (SD: 1.9) years, and the mean duration of nodding syndrome from diagnosis to enrollment was 8.3 (SD: 2.7) years. The majority with nodding syndrome had been exposed to O volvulus (147/154 (95.4%)) compared with community children (86/154 (55.8%)), with an OR of 17.04 (95% CI: 7.33, 45.58), P < .001. C5a was elevated in CSF of children with nodding syndrome compared to controls (P < .0001). The levels of other CSF markers tested were comparable between cases and controls after adjusting for multiple comparisons. Children with nodding syndrome had lower plasma levels of IL-10, APRIL, CCL5 (RANTES), CCL2, CXCL13, and MMP-9 compared with community controls (P < .05 for all; multiple comparisons). Plasma CRP was elevated in children with nodding syndrome compared to community children and correlated with disease severity.
Keywords: Nodding syndrome; Children and adolescents; Cerebrospinal fluid immune